2022
DOI: 10.1016/j.auec.2021.12.001
|View full text |Cite
|
Sign up to set email alerts
|

A multidisciplinary, cross-sectional survey of burnout and wellbeing in emergency department staff during COVID-19

Abstract: BACKGROUND Emergency department (ED) staff are at-risk of burnout, poor wellbeing and increased stress that can impact patient satisfaction, staff morale and retention. The aim of this survey was to determine level of burnout, stress and satisfaction with current employment role in ED during COVID-19. METHODS A multisite cross-sectional survey captured ED employment data, wellbeing, burnout (Maslach Burnout Inventory), stress (Health Professions Stress Inventory), work … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 26 publications
(31 reference statements)
1
15
0
3
Order By: Relevance
“…We also aimed to compare medical categories in terms of burnout dimensions. Based on previous literature presented above [ 2 , 10 ], we expected to find a higher rate of burnout among nurses compared with physicians, medical residents, and orderlies.…”
Section: Introductionmentioning
confidence: 92%
See 4 more Smart Citations
“…We also aimed to compare medical categories in terms of burnout dimensions. Based on previous literature presented above [ 2 , 10 ], we expected to find a higher rate of burnout among nurses compared with physicians, medical residents, and orderlies.…”
Section: Introductionmentioning
confidence: 92%
“…In recent years, burnout syndrome has been a widely discussed issue among medical staff. At almost two years after the onset of the biggest pandemic of the modern world and one year after the first anti-COVID vaccine became available, the literature points to increasing burnout among healthcare workers all over the word [ 1 , 2 , 3 ]. Before the COVID-19 pandemic, the statistics showed that more than 400 doctors took their own lives every year but now, due to depression and exhaustion, there has been a sharp increase in these statistics [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations